2017
DOI: 10.1177/1557988317695901
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on Occurrences of Depression and Anxiety and Associated Risk Factors in the Infertile Chinese Men

Abstract: The prevalence of depression and anxiety in the Chinese male population with infertility is still uncertain. The prevalence of depression, anxiety, and a combination of both psychological symptoms was 20.8%, 7.8%, and 15.4%, respectively in 771 infertile Chinese men in the current study by the Mental Health Inventory–5 and the State–Trait Anxiety Inventory–Short Form questionnaires. Differences in demographics (age, education, and income) had no noticeable impact on the development of psychological symptoms. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 39 publications
1
46
1
4
Order By: Relevance
“…23 There are many studies evaluating psychological well-being of patients with infertility, especially their anxiety and depression levels. 2,[4][5][6][7][8][9][10][11][12]24 Increased stress-related anxiety and depression have been shown to reduce the success of in vitro fertilization by affecting cytokine levels. 11 In addition, it has been emphasized that semen parameters were adversely affected as a result of changes in the blood hormonal levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 There are many studies evaluating psychological well-being of patients with infertility, especially their anxiety and depression levels. 2,[4][5][6][7][8][9][10][11][12]24 Increased stress-related anxiety and depression have been shown to reduce the success of in vitro fertilization by affecting cytokine levels. 11 In addition, it has been emphasized that semen parameters were adversely affected as a result of changes in the blood hormonal levels.…”
Section: Discussionmentioning
confidence: 99%
“…3 Anxiety and depressive disorders were reported to be more common in infertile individuals. 2,[4][5][6][7][8][9] It has been reported that the incidence of psychiatric disorders in both male and female infertility is 12.41% after 2 years of diagnosis and that psychiatric support might be needed during the diagnosis and the treatment of infertility. 8 In addition, a change in the blood and semen levels of hormonal and oxidative stress products has been shown to depend on the level of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most infertile men and women find themselves to be the targets of gossip from their relatives, peers, extended family members, and the broader community. For example, some participants reported that siblings and neighbors labelled them as being “incomplete people,” belonging to an “imperfect family,” and living a “life of regret” (Chen et al, ; Yang et al, ). This increased their feelings of humiliation and misery.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is often considered to be a decrease or loss of fertility. Therefore, patients with male infertility will suspect their masculinity, especially in men with sexual dysfunction or azoospermia who bears strong feelings of inferiority and guilty [14] . This study showed that male infertility is one of the factors that affect the QOL of patients with repeated implantation failure ( Table 6).…”
Section: Attribution Of Infertilitymentioning
confidence: 99%